2012
DOI: 10.1002/ajpa.22130
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio (2D:4D) and handgrip strength in subjects of Han ethnicity: Impact of sex and age

Abstract: The ratio of the length of the second finger to the fourth finger (2D:4D) is considered to be a putative proxy of prenatal exposure to testosterone, and has been increasingly used as a promising tool to evaluate the impact of prenatal androgenization in humans in such traits as physical performance. In this study, for the first time, we present 2D:4D data on adult participants of Han ethnicity. We consider the sexual dimorphism of 2D:4D and handgrip strength, and also report the relationship between 2D:4D and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 66 publications
(72 reference statements)
5
37
3
Order By: Relevance
“…Similar results were found in studies from Han ethnicity. 33 Studies on Hui and Han ethnicities of the Chinese population reported a negative correlation of 2D:4D ratio of both hands with HGS in women. 30,31 Other studies on the left hand report no correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in studies from Han ethnicity. 33 Studies on Hui and Han ethnicities of the Chinese population reported a negative correlation of 2D:4D ratio of both hands with HGS in women. 30,31 Other studies on the left hand report no correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Fink et al, (2006) and Zhao et al, (2012) suggested that there was a negative correlation between 2D:4D and GS, whereas Zhao et al, (2012) and Hone and McCullough (2013) confirmed that there was not a correlation in the females for the same variable. Furthermore, there are many studies proving that there is no correlation between 2D:4D and static strength (van Anders, 2007;Gallup et al, 2007, Halil andGürel, 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Zhao et al, (2015) suggested that there was a strong correlation between the cardiovascular system and muscle strength due to prenatal testosterone in the males but reported no evidence for the females. In studies examining the correlation between 2D:4D and strength, Grip Strength (GS) test which determines the static strength is utilized (Ranson et al, 2015;Bilgiç et al, 2016;Eghbali, 2016;van Anders, 2007;Gallup et al, 2007;Zhao et al, 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies on 2D:4D in humans provide clear evidence for sexual dimorphism (Manning et al, 1998;Manning, 2002;Saino et al, 2006;Grimbos et al 2010;Nelson et al, 2011;Zhao et al, 2012). Non-human studies conducted so far have, however, yielded inconsistent results, although sexual dimorphism in 2D:4D has been found in some of the tested species, including amphibians (Oophaga pumilio: Chang, 2008) Romano et al, 2005;Saino et al, 2007), and mammals (rodents: Brown et al, 2002;Manning et al, 2003;Leoni et al, 2005;Yan et al, 2008;primates: Roney et al, 2004;McIntyre et al, 2009;Nelson and Shultz, 2010).…”
mentioning
confidence: 99%